Technology And The Deterioration Of Right To Privacy - Wan Mohd Nor, Murni; Mohd Asraf, Ratnawati (Penerbit Universiti Sains Malaysia (USM Press), 2011)
The infringement of privacy is a rising phenomenon, which is only accelerated as technology advances. This article provides a critical review of the concept of right to privacy, the cases involving deterioration of privacy due to technology and the legal position in reference to its violation. It has become evident that at present, Malaysia's response to such infringements and violations is far from satisfactory and leaves much to be desired. This article argues that Malaysian law, with regard to privacy protection, is below the acceptable standard. This is in contrast to many developed, democratic countries such as the United States, which have placed more emphasis in developing their privacy laws and policies. It is hoped that this article can highlight the lacunae in Malaysian privacy law and put to the fore the consequences that will ensue as a result of the law's failure in safeguarding privacy. It concludes by emphasising the need to legislate better laws to adequately address the magnitude of problems concerning the derogation of privacy and providing suggestions as to the steps need to be taken in order to ensure that the right to privacy is protected and upheld